Partially non‐linear stimulation intensity‐dependent effects of direct current stimulation on motor cortex excitability in humans - Batsikadze, G.; Moliadze, V.; Paulus, W.; Kuo, M.‐F.; Nitsche, M. A. (The Journal of physiology, 2013)
Key points • Application of 2 mA cathodal transcranial direct current stimulation for 20 min results in cortical excitability enhancement instead of inhibition. • Longer or more intensive stimulation does not necessarily increase its efficacy. • Short intracortical inhibition and facilitation are shifted towards excitability enhancement after both 2 mA anodal and cathodal stimulation. • I‐waves, input–output curves and cortical silent period are unaffected immediately after 2 mA stimulation. Transcranial direct current stimulation (tDCS) of the human motor cortex at an intensity of 1 mA with an electrode size of 35 cm2 has been shown to induce shifts of cortical excitability during and after stimulation. These shifts are polarity‐specific with cathodal tDCS resulting in a decrease and anodal stimulation in an increase of cortical excitability. In clinical and cognitive studies, stronger stimulation intensities are used frequently, but their physiological effects on cortical excitability have not yet been explored. Therefore, here we aimed to explore the effects of 2 mA tDCS on cortical excitability. We applied 2 mA anodal or cathodal tDCS for 20 min on the left primary motor cortex of 14 healthy subjects. Cathodal tDCS at 1 mA and sham tDCS for 20 min was administered as control session in nine and eight healthy subjects, respectively. Motor cortical excitability was monitored by transcranial magnetic stimulation (TMS)‐elicited motor‐evoked potentials (MEPs) from the right first dorsal interosseous muscle. Global corticospinal excitability was explored via single TMS pulse‐elicited MEP amplitudes, and motor thresholds. Intracortical effects of stimulation were obtained by cortical silent period (CSP), short latency intracortical inhibition (SICI) and facilitation (ICF), and I wave facilitation. The above‐mentioned protocols were recorded both before and immediately after tDCS in randomized order. Additionally, single‐pulse MEPs, motor thresholds, SICI and ICF were recorded every 30 min up to 2 h after stimulation end, evening of the same day, next morning, next noon and next evening. Anodal as well as cathodal tDCS at 2 mA resulted in a significant increase of MEP amplitudes, whereas 1 mA cathodal tDCS decreased corticospinal excitability. A significant shift of SICI and ICF towards excitability enhancement after both 2 mA cathodal and anodal tDCS was observed. At 1 mA, cathodal tDCS reduced single‐pulse TMS‐elicited MEP amplitudes and shifted SICI and ICF towards inhibition. No significant changes were observed in the other protocols. Sham tDCS did not induce significant MEP alterations. These results suggest that an enhancement of tDCS intensity does not necessarily increase efficacy of stimulation, but might also shift the direction of excitability alterations. This should be taken into account for applications of the stimulation technique using different intensities and durations in order to achieve stronger or longer lasting after‐effects.